Peran Employee Engagement dalam Meningkatkan Loyalitas Karyawan - Ridho Lazuardi Wahyudi; Odi Jarodi (Universitas 45 Surabaya, 2025)
This research aims to analyze the concept of employee engagement and its relationship with employee loyalty in the context of organizational change. With a qualitative approach based on literature study, this research explores data from various secondary sources, such as scientific journals, books, and organizational reports. The analysis shows that employee engagement contributes significantly to employee loyalty. Emotionally and intellectually engaged employees show higher commitment to the organization, reduce turnover rates, and increase productivity. Strategies such as creating an inclusive work environment and career development opportunities are considered effective for increasing employee engagement. The findings provide practical insights for companies to strengthen relationships with employees in the face of global challenges.